Laboratory testing for suspected COVID‐19 vaccine–induced (immune) thrombotic thrombocytopenia - Favaloro, Emmanuel J. (International journal of laboratory hematology, 2021)
COVID‐19 (coronavirus disease 2019) represents a pandemic, and several vaccines have been produced to prevent infection and/or severe sequelae associated with SARS‐CoV‐2 (severe acute respiratory syndrome coronavirus 2) infection. There have been several reports of infrequent post vaccine associated thrombotic events, in particular for adenovirus‐based vaccines. These have variously been termed VIPIT (vaccine‐induced prothrombotic immune thrombocytopenia), VITT (vaccine‐induced [immune] thrombotic thrombocytopenia), VATT (vaccine‐associated [immune] thrombotic thrombocytopenia), and TTS (thrombosis with thrombocytopenia syndrome). In this report, the laboratory test processes, as utilised to assess suspected VITT, are reviewed. In published reports to date, there are notable similarities and divergences in testing approaches, potentially leading to identification of slightly disparate patient cohorts. The key to appropriate identification/exclusion of VITT, and potential differentiation from heparin‐induced thrombocytopenia with thrombosis (HITT), is identification of potentially differential test patterns. In summary, testing typically comprises platelet counts, D‐dimer, fibrinogen, and various immunological and functional assays for platelet factor 4 (PF4) antibodies. In suspected VITT, there is a generally highly elevated level of D‐dimer, thrombocytopenia, and PF4 antibodies can be identified by ELISA‐based assays, but not by other immunological assays typically positive in HITT. In addition, in some functional platelet activation assays, standard doses of heparin have been identified to inhibit activation in suspected VITT, but they tend to augment activation in HITT. Conversely, it is also important to not over‐diagnose VITT, given that not all cases of thrombosis post vaccination will have an immune basis and not all PF4‐ELISA positive patients will be VITT.